Radiation Induced Osteosarcoma of the Larynx: A Rare Case Report - Thomas, Smrithi Sara; Nair, Vijayalakshmi; Kutti, Sajna VM; KS, Vijayagopal (Annals of Pathology and Laboratory Medicine, 2024)
Secondary malignancies caused by radiation, especially radiation-induced sarcomas (RIS), are perhaps the most severe late side effects of radiotherapy. The incidence of sarcomas after irradiation is estimated to be as high as 0.3% in those who have survived neck and head cancer for a long time. Nevertheless, it is also accompanied by significant morbidity and mortality. RIS of the head and neck is not prevalent. As there are only a limited number of case reports, we report a case of radiation induced osteosarcoma from our institution. Case report: A 67 year old male patient, previously treated for squamous cell carcinoma larynx with radiotherapy 60 gy, presented to our institution with complaints of hoarseness of voice. CT Neck showed an ill-defined heterogeneously enhancing mass lesion in the larynx with extra laryngeal extension and causing erosion of the thyroid cartilage. He was subsequently taken for total laryngectomy. Histopathological examination showed a high-grade malignant neoplasm. Further IHC revealed tumor cells diffusely positive for SATB2 and negative for PanCK, p63 and p40. He was diagnosed with high grade osteosarcoma and was taken up for adjuvant chemotherapy. Conclusion: As there are only limited case reports, more number of cases should be reported for further discussion about the adjunctive treatment options and prognosis.